2014
DOI: 10.1186/1471-2164-15-1104
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased chromatin accessibility profiling by RED-seq uncovers unique features of nucleosome variants in vivo

Abstract: BackgroundDifferential accessibility of DNA to nuclear proteins underlies the regulation of numerous cellular processes. Although DNA accessibility is primarily determined by the presence or absence of nucleosomes, differences in nucleosome composition or dynamics may also regulate accessibility. Methods for mapping nucleosome positions and occupancies genome-wide (MNase-seq) have uncovered the nucleosome landscapes of many different cell types and organisms. Conversely, methods specialized for the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…To study the dynamics of gene regulatory activity in response to environmental and developmental clues, mapping chromatin accessibility remained an important task over decades. While DNase-I has been a preferred choice to digest the open chromatin due to relatively lesser sequence specificity of the enzyme, only few studies attempted restriction endonucleases to identify accessible regions in the chromatin [46,54,55]. On the contrary, restriction endonucleases have been extensively used to digest the chromatin, presumably in an unbiased manner, in proximity ligation based techniques like 3C, 4C, 5C and Hi-C [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the dynamics of gene regulatory activity in response to environmental and developmental clues, mapping chromatin accessibility remained an important task over decades. While DNase-I has been a preferred choice to digest the open chromatin due to relatively lesser sequence specificity of the enzyme, only few studies attempted restriction endonucleases to identify accessible regions in the chromatin [46,54,55]. On the contrary, restriction endonucleases have been extensively used to digest the chromatin, presumably in an unbiased manner, in proximity ligation based techniques like 3C, 4C, 5C and Hi-C [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Regional depletions in read counts obtained from digested chromatin when compared with the reads obtained from digested naked DNA would mark the biased restriction digestion of chromatin. Towards this, we obtained the 'Restriction Endonuclease Digestion coupled with sequencing' (REDseq) data of in-situ restriction digested chromatin and in-solution restriction digested naked DNA of mouse embryonic stem cells (mESC) from Chen et al [46]. We calculated the read counts for 10 kb bins of the mouse genome and normalized by the total reads.…”
Section: Biased Visibility In Hi-c Data Marks Condensed and Decondensmentioning
confidence: 99%
“…To study the dynamics of gene regulatory activity in response to environmental and developmental clues, mapping chromatin accessibility remained an important task over decades. While DNase-I had been a preferred choice to digest the chromatin due to relatively lesser sequence specificity of the enzyme, only few studies had attempted restriction endonucleases to identify accessible regions in the chromatin 41,47,48 . On the contrary, restriction endonucleases have been extensively used to digest the chromatin, presumably in an unbiased manner, in proximity ligation based techniques like 3C, 4C, 5C and HiC [6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…We first showed that the in-situ restriction digestion of chromatin was not uniform in the genome. Towards this, we obtained the sequencing data for in-situ restriction digested chromatin and in-solution restriction digested naked DNA of mouse embryonic stem cells (mESC) 41 . We calculated the read counts for 10 kb bins of the mouse genome and normalized by the total reads.…”
Section: Biased Visibility In Hic Data Marks Condensed and Decondensementioning
confidence: 99%
“…Other experimental techniques measure nucleosome binding genome-wide, e.g. MPE-Seq (Ishii, Kadonaga, and Ren 2015), RED-Seq (Chen et al 2014), NOMe-Seq (Kelly et al 2012); nucleosome binding at individual loci, e.g. by electron microscopy (Brown et al 2013), by DNA methylation (Small et al 2014); or nucleosome binding to short DNA fragments in vitro, e.g.…”
Section: Introductionmentioning
confidence: 99%